In or Out? The Welfare Costs of EMU Membership - Ferreira-Lopes, A. (Economic Modelling, 2010)
Sweden and the UK have repeatedly refused to join the European and Monetary Union (EMU). Surprisingly, there is very little work on the welfare consequences of the loss of monetary policy flexibility for these countries. This paper fills this void by providing a framework to evaluate quantitatively the economic costs of joining the EMU. Using a two-country dynamic general equilibrium model with sticky prices we investigate the economic implications of the loss of monetary policy flexibility associated with the EMU for each country. The main contribution of our general equilibrium approach is that we can evaluate the effects of monetary policy in terms of welfare. Our findings suggest that these economies may experience sizable welfare losses as a result of joining the EMU. Results show that the cost associated with the loss of the monetary policy flexibility is higher in the presence of persistent government consumption shocks and small trade shares with the EMU.